Fractals in carbon nanotube buckypapers. Issue 11 (21st January 2016) - Zhang, Chunyong; Cui, Haiyan; He, Zhenzhu; Su, Lin; Fu, Degang
Abstract : Here, the fractal properties of buckypapers (BPs) have been initially studied by SEM imaging at different scales, as well as by low-pressure nitrogen adsorption analysis. Abstract : Here, the fractal properties of buckypapers (BPs) have been initially studied by SEM imaging at different scales, as well as by low-pressure nitrogen adsorption analysis. The BPs under investigation are composed of either single-walled carbon nanotubes (SWNTs) or multi-walled carbon nanotubes (MWNTs). Fractal analysis of either film morphology or adsorption isotherm shows that the fractal dimension of SWNT-BPs is higher than that of the MWNT-BPs. As a result, such difference offers a new and important explanation for their differing adsorption capabilities during decontamination processes.